HUBUNGAN PEMAHAMAN MUATAN MATERI KEAHLIAN INTI PROGRAM STUDI DENGAN WAWASAN KERJA PASCA PELAKSANAAN PRAKTIK INDUSTRI MAHASISWA PENDIDIKAN TEKNIK BANGUNAN - Febri Sudarmanto, - (2022)
One of the career choices of Building Engineering Education students is to have a career in civil engineering. However, there is a difference between understanding the content of the core expertise of the study program and the actual work in the field to find out that work in the field requires work insight. This study aims to find out the general description of the relationship between understanding the content of the core expertise of the study program with work insight after the implementation of industrial practices for students of Building Engineering Education. The method used in this study is a correlational method with a quantitative approach that describes the current situation. The objects in this study are students of the 2018 Building Engineering Education Program who are still actively studying as many as 75 students, and for the respondents, the entire object of the research is 75 students. Data collection with questionnaire method (questionnaire). The data analysis technique in this study used correlation statistics with parametric statistical tests. And the results of the study obtained a general description of the understanding of the content of the core expertise of the Building Engineering Education student study program which has an average percentage of 75.116%. An overview of work insights after the implementation of industrial practices for Building Engineering Education students has an average percentage of 78.007%. Based on the results of research using the Pearson Product Moment correlation technique , the correlation coefficient is obtained r_xy=0,813. This shows that there is a relationship, so it can be concluded that this research "there is a significant relationship between the understanding of the content of the core expertise of the study program and the insight of work after the implementation of industrial practice for building engineering students. For researchers who are interested in studying and examining more broadly and deeply the problems related to this research, it is better to use variables and a wider population so that new research can be obtained as a comparison.